Engineering design toward exploring the functional group substitution in 1D channels of Zn-organic frameworks upon nitro explosives and antibiotics detection - Zhou, Zhan; Han, Min-Le; Fu, Hong-Ru; Ma, Lu-Fang; Luo, Feng; Li, Dong-Sheng (Dalton transactions : an international journal of inorganic chemistry, 2018)
Three isostructural metal-organic frameworks denoted as Zn(L)(aip)·(H 2 O) ( 1 ), Zn(L)(ip)·(DMF)(H 2 O) 1.5 ( 2 ), and Zn(L)(HBTC)·(H 2 O) 2 ( 3 ) with functional groups -NH 2 , -H and -COOH, respectively, decorated on the 1D channels have been rationally designed with the purpose of exploring the influence of electron transfer from organic ligands in the 1D channels on the sensing of nitro explosives and antibiotics. These three compounds exhibit strong fluorescence in water, and they can be applied to detect the presence of explosives or antibiotics by means of fluorescence quenching in aqueous solution, whereas in terms of special explosives or antibiotics at the same concentration, 3 demonstrates a more superior quenching efficiency than 1 and 2 . More importantly, it has been found that the difference in the sensing performances of these compounds is closely related to the interaction between the functional groups and guest molecules via electron and energy transfer from MOFs to explosives and antibiotics. Three MOFs ( 1 , 2 , 3 ) with distinct functional groups were prepared. 2 exhibited moderate sensitivity for the detection of specific explosives/antibiotics at the same concentration, which was lower and higher than that of 3 and 1 , respectively.